Propensity of self-assembled leucine-lysine diblock copolymeric alpha-helical peptides to remain in parallel and antiparallel alignments in water - Sarkar, Sujit; Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2015)
Molecular dynamics Simulation study of alpha-helical diblock copolypeptides: preassembled in parallel and antiparallel alignments in water are presented. The assembled peptide lamellar structures were not disrupted even: after performing three step simulation protocols. Primarily hydrogen bonds between peptide are responsible for the stability: The analysis of the trajectory also suggests that Water plays a significant role in favoring self assembly We have detected continuous hydrogen bonded network structure, which is further responsible for the stability Of the lamellar structures. We have performed a detailed analysis of the hydrogen bonded network structure and its length. Further, free energy calculations revealed that the degree of stability for both lamellae are similar. The present study provides structural insight into the stability of self-assembled structures of block copolypeptides.